An Examination of a Method to Reduce the Effect of Standing-Wave Heat Generation in Ultrasound-Excited Thermography Inspection - So Takahashi; Masashi Ishikawa; Hideo Nishino; Masashi Koyama; Ryo Fukui (Engineering Proceedings, 2023)
A non-destructive inspection technique using infrared thermography and ultrasound excitation (ultrasound-excited thermography method) was focused on in this study. Although this method is effective in the detection of closed defects, the standing waves are generated in the inspection object, and this causes periodic heat distribution in the non-defective area. Such standing wave heat distribution can lead to the misdetection of defects and result in a reduction in inspection capability. In this study, in order to suppress the influence of standing wave heat distribution, we examined a method to average thermal images obtained under different ultrasonic excitation conditions. The experimental results showed that averaging the thermal images obtained when exciting ultrasound at several different points was effective in suppressing the unwanted standing wave heat distributions.